Small ruminant production in mixed farming systems: Case studies in research design - Okali, C.; Knipscheer, H.C. (Kansas State University, 1986)
Describes the small ruminant production systems in Java, Indonesia and in the humid zone of West Africa. Highlights key feautures of small farm systems which should determine on-farm research design.